Effectiveness of government's effort in the training of mature employees - Lee, Siau Lee (2014)
Since mature employees are such important assets to the nation, we would like to find out what are the variables that affect the government's effectiveness in the effort of training the mature employees. We have gathered some variables from the preliminary interviews conducted, namely, attitudes of employers towards training, knowledge of government's training programmes by employers, attitudes of employees towards training, knowledge of government's training programmes by employees. From our findings, these variables do have a significant relationship with the effectiveness of the government effort in training of these workers. We would suggest that the government should educate the mature employees on the importance of training and also increase the awareness of such training programmes through the mass media.